2014
DOI: 10.5398/medpet.2014.37.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Porang by Streptomyces violascens BF 3.10 Mannanase for the Production of Mannooligosaccharides

Abstract: Porang (Amorphophallus muelleriBlumeo C dengan aktivitas enzim sebesar 16.38 U/mL dan stabil pada suhu 4 °C selama 48 jam. Selama 5 jam waktu hidrolisis, reaksi dengan konsentrasi substrat 0,25%, 0,5%, dan 1% glukomanan porang yang dilarutkan dalam 10 mL enzim menghasilkan manooligosakarida dengan derajat polimerisasi 2-3. Visualisasi produk hidrolisis mengggunakan metode thin layer chromatography (TLC) dan high performance liquid chromatography (HPLC) menunjukkan bahwa jenis manooligosakarida yang dihasilkan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…According to Harmayani et al (2014), PGM flour contains glucomannan almost the same around 92.69% of glucomannan. Meanwhile, the glucomannan content in porang powder roughly of 75.72% (Safitri et al, 2014). As a result that PGM was consisted of lipid (2.52 g/100 g ±0.10), crude fiber (0.37 g/100 g ±0.05), protein (0.33 g/100 g ±0.08), ash (0.66 g/100 g ±0.02) and water (8.48 g/100 g ±0.15).…”
Section: Proximate Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…According to Harmayani et al (2014), PGM flour contains glucomannan almost the same around 92.69% of glucomannan. Meanwhile, the glucomannan content in porang powder roughly of 75.72% (Safitri et al, 2014). As a result that PGM was consisted of lipid (2.52 g/100 g ±0.10), crude fiber (0.37 g/100 g ±0.05), protein (0.33 g/100 g ±0.08), ash (0.66 g/100 g ±0.02) and water (8.48 g/100 g ±0.15).…”
Section: Proximate Analysismentioning
confidence: 99%
“…The reducing sugar of POG was obtained under optimal conditions (1:1000 of E/S, 5.5 pH, and 37 o C) is summarized in Figure 1. The amount of reducing sugar shows the ability of mannanase to hydrolyze porang glucomannan (Safitri et al, 2014). Accordingly, Chen et al (2013) reported that oligosaccharides production is influenced precisely by reducing sugar present.…”
Section: Degree Polymerization Of Pogmentioning
confidence: 99%
See 2 more Smart Citations
“…12 . Glucomannan also potential as a source of monooligosaccharide prebiotics due to its modulating effect to the microflora in the gastrointestinal tract 13 . Glucomannan mechanism of the modulating effect has been shown to be similiar with other soluble fibers i.e., fermentable fiber.…”
mentioning
confidence: 99%